(untitled) (Jurnal Pendidikan Fisika, 2025)
Scientific reasoning is a core skill in science education because it allows students to think logically, critically, and systematically when approaching problems and understanding natural phenomena. Yet, international assessments such as PISA and TIMSS have repeatedly shown that Indonesian students lag behind global averages in this area, making it an urgent issue for physics education. This study aimed to assess the scientific reasoning abilities of grade XI students in Surakarta using a motion dynamics testlet adapted from Lawson’s Classroom Test of Scientific Reasoning (LCTSR). The research employed a descriptive quantitative design and involved 363 students from three high schools representing different school locations and levels of practicum experience. The testlet, developed through stages of planning, piloting, and validation, was designed to ensure reliability and to capture reasoning indicators such as conservation, proportionality, variable control, probability, correlation, and hypothetico-deductive reasoning. The results revealed that most students were in the concrete (51%) and transitional (47%) stages of operation, with only 2% reaching the formal operational stage. In terms of achievement categories, the majority fell into the fair and lower levels, and none reached the very good level. Statistical analysis showed no significant gender differences, but students from urban schools and those with practicum experience performed significantly better. The novelty of this research lies in contextualizing Lawson’s instrument in terms of motion dynamics and adopting a testlet format that efficiently measures reasoning. These findings highlight the central role of the school environment and practical experience in shaping reasoning skills and provide valuable evidence for strengthening physics teaching and policy.